A alma e o livre-arbítrio em Santo Agostinho: uma trajetória da pedagogia do Circuitum nostrum - Santos, Wilton Lima dos (2014)
This thesis is based mainly on the books About the Potentiality of the Soul: De quantitate animae and De libero arbítrio written by Saint Augustine. We discourse about the process of conceptualization of the being soul and of the solution of the problem of free choice through the Augustinian pedagogical system circuitum nostrum. We will see that this immaterial being which makes us rational, and therefore human, is what comes closest to God of all the beings of the creation. An immortal being, with innate ideas, without division and which monitors all the functions of the body, making it possible for the human being to use the memory, reason and rationality. Subsisting in itself, it remains, even after the separation from the body, as a whole entity and carrier of all the memories of the body which animated it for life. Presenting himself as a dualist, St. Augustine reveals to us that although the soul is in the body it is not bound to the body, but is in the body. Without growth and aging this immaterial being without dimensions is real, however unknown to the subject him/her self who houses it. A being which maintains the vital principle and that of animation (animus) of the body. When this soul is educated by rationality it permits the human being the full use of freedom in the moral choice of action, or free will. We will see the influence of Socrates, Plato and neoplatonism through the dialogs inserted in the Augustinian pedagogical system circuitum nostrum and the relation between the pedagogism of Paulo Freire as a mirror of augustinianism, through the dialog as producers of active subjects in the transformation of society.